Association of Oxelytrum cayennense (Silphidae, Coleoptera) with Pig Carcasses (Sus scrofa, Suidae) in Terra Firme Areas in Manaus, Amazonas, Brazil - Ururahy-Rodrigues, Alexandre; Rafael, José Albertino; Pujol-Luz, José Roberto; Henriques, Augusto Loureiro; Queiroz, Margareth Maria de Carvalho; Barbosa, Rodrigo Rocha; Baroni, Marcus Neves (EntomoBrasilis, 2010)
Colonization aspects of the carrion beetle Oxelytrum cayennense (Sturm) in man-size pig carcasses (~60 kg) are presented at Adolpho Ducke Forest Reserve, Manaus, Brazil. This species colonized pig carcasses from bloated to skeletonized stages. Adults were eventually observed preying on fly larvae from the second day postmortem and their larvae were observed from the fifth day postmortem feeding on skeletonized areas, probably cleaning the bones of the remaining soft tissues. Adult beetles with predatory behavior on the oldest Diptera larvae can impact their populations and thereby complicate the estimation of the time of death as these larvae are frequently used as a postmortem indicator. In addition, both larvae and adult developmental stages have potential use as a postmortem interval (PMI) indicator because the adult can colonizes carcasses from the second postmortem day onward and the larvae from the fifth day onward. Associação de Oxelytrum cayennense, (Silphidae, Coleoptera) com Carcaças de Porcos (Sus scrofa, Suidae) em Áreas de Terra Firme em Manaus, Amazonas, Brasil Resumo. Aspectos da colonização do silfídeo Oxelytrum cayennense (Sturm) em carcaças de porcos do tamanho de um homem adulto na Reserva Florestal Adolpho Ducke são apresentados. Esta espécie colonizou as carcaças de porcos do estágio enfisematoso à esqueletização. Adultos foram observados eventualmente predando larvas de moscas a partir do segundo dia de intervalo pós-morte e suas larvas foram observadas a partir do quinto dia se alimentando em áreas esqueletizadas, provavelmente limpando os ossos dos tecidos moles remanescentes. O comportamento predatório dos adultos nas larvas de dípteros mais velhas podem impactar suas populações e complicar estimativas de intervalo pós-morte, uma vez que estas são freqüentemente usadas para esta estimativa. Além disso, adultos e larvas têm potencial uso como indicadores de intervalo pós-morte (IPM) porque o adulto pode colonizar carcaças do segundo dia em diante e as larvas do quinto dia em diante.